Alone Together Dengan Perubahan Perilaku Emosional Remaja Dalam Keluarga - Ramadhanintyas, Karina Nur; Rahmawati, Arista Dwi; Wibowo, Pipid Ari (Universitas Tribhuwana Tunggadewi, 2023)
Alone together is a condition when humans have more expectations of technology but less to connect. The presence of this phenomenon may be disrupted family functions such as socialization between family members emotionally. The condition may occur in adolescents who have an excessive duration of cell phone use (addiction). To know that 10 out of 12 students of SMPN 01, Dagangan, Madiun use cell phones for more than 10 hours daily. The study's purpose is to determine the association between the alone together phenomenon and adolescents’ emotional behavior in the family. This study used a quantitative with a cross-sectional design, with data obtained through questionnaires and interviews. The population in this study was students of SMPN 01 Dagangan, Madiun with a total of 133 students. The sample was calculated using the Slovin formula with a margin of error of 0.1 and recruited 57 participants (27 women and 30 males) with an average age of 12-16 years old. Purposive sampling was used. Data were analyzed using the contingency coefficient test. The results showed a p-value of 0.0670.1 with a correlation coefficient of 0.236, which means there was a weak relationship among variables. Suggestions for further research are expected to elaborate on other variables such as psychosocial factors and parenting models.